Study on 3-D modification for reducing vibration of helical gear based on TCA technology, LTCA technology and system dynamics. (1st January 2021) - Wang, Cheng
Highlights: TCA, LTCA and dynamic analysis is used to complete the 3-D modification. A parabolic modification along helix direction is described in axial modification. The results show good vibration reduction effect by using the proposed method. Abstract: Vibration and noise of gear meshing come from the dynamic working conditions, therefore, combining gear modification and dynamic characteristic analysis may offer reliable basis for the modification. Compared with profile modification and axial modification, 3-D modification is more comprehensive. The existing problems in current gear modification includes: (1) The ideal force under static or quasi-static conditions is used to replace the transient dynamic meshing force, so the effect of modification is not obvious in the middle and high speed gear transmission. (2) Though the modification is completed according to the dynamic performance, the dynamic characteristic analysis is not well combined with the gear meshing performance. Tooth contact analysis (TCA) and loaded tooth contact analysis (LTCA) can simulate the meshing process of gear and provide precise tooth surface geometric analysis data for later dynamic characteristic analysis. Therefore, combining TCA technology, LTCA technology and dynamic performance of gear, a 3-D modification method for reducing vibration of helical gear is proposed. Two application examples are given and good vibration reduction effects have been obtained. The biggest highlight of the paper is to use TCA technology, LTCA technology and dynamic characteristic analysis of gear to complete the 3-D modification of helical gear.